Kampanye Digital di Marketplace: Studi Resepsi Followers Akun Tokopedia di Instagram - Hamidah, Riqqah; Saragih, Nurhayani (Jurnal Mahardika Adiwidia, 2025)
This study aims to examine audience reception of the "Kejutan Belanja Untung" promotional campaign posted by the @tokopedia Instagram account during the 2022 period. The analysis draws on Stuart Hall’s encoding/decoding reception theory and considers four key consumer psychological factors: motivation, perception, learning, and attitude. Employing a constructivist paradigm, the study uses a descriptive qualitative approach with a reception analysis method. Data validity was ensured through source triangulation, and data were collected through in-depth interviews with seven informants who follow the @tokopedia Instagram account. The findings indicate that all seven informants exhibited a dominant-hegemonic reading in terms of motivation and attitude. However, their perception and learning responses varied, with some aligning with the dominant-hegemonic position and others reflecting an oppositional reading.